Prescription patterns for psychotropic drugs in cancer patients; a large population study in the Netherlands - Guan, N.C.; Boks, M.P.; Smeets, H.M.; Zainal, N.Z.; de Wit, N.J. (2012)
BACKGROUND: Psychotropic drugs are commonly prescribed for various psychological complaints in cancer patients. We aim to examine the prescription pattern in cancer patients of three common psychotropic drugs: benzodiazepine, antidepressant and antipsychotic. METHODS: This is a retrospective case-control study. Data were extracted from the Agis Health Database. This insurance database contains the healthcare consumption of 1.3 million inhabitants of the Netherlands. We analyzed the use of psychotropics in cancer patients and an equally sized randomly selected control group of noncancer patients from 2006 to 2008. Odds ratio (OR) were adjusted for age, gender, immigrant status, neighborhood socio-economic status, and premorbid medical condition. Additionally, the numbers of new user in the 3 months after cancer was diagnosed and in the 3 months before death were compared. RESULTS: A total of 113 887 cancer patients and 121 395 control subjects were included. Cancer patients were significantly more often prescribed psychotropic drugs (adjusted OR: benzodiazepines = 1.70, CI = 1.67-1.74; antidepressants = 1.38, CI = 1.34-1.42; and antipsychotics = 1.70, CI = 1.62-1.77). Lower socio-economic status, immigrant, and premorbid chronic medical conditions were significantly associated with higher risk of psychotropic use. Odds for a new prescription for all three psychotropic drugs were significantly less in the first 3 months after cancer diagnosis than the 3 months before death (benzodiazepine, OR = 0.673, CI = 0.647-0.705; antidepressant, OR = 0.592, CI = 0.544-0.644; antipsychotic, OR = 0.177, CI = 0.165-0.190) CONCLUSIONS: Psychotropic drug prescription is common in cancer patients, starts soon after diagnosis, and increases in the terminal stage. Prescription rates were significantly higher in patients from lower socio-economic group, immigrants, or with premorbid chronic medical condition.Copyright © 2012 John Wiley & Sons, Ltd.